Exploring academics’ knowledge sharing intention on institutional innovation capability - Mohammad , Mozammel Haque; Ahlan, Abdul Rahman; Mohamed Jalaldeen , Mohamed Razi (2014)
In today’s knowledge-based-society, academics are the intellectual leaders for the developing of societies. As intellectual leaders, academics’ Knowledge Sharing (KS) intention on innovation may be seen as having an important role in the Higher Education Institutions (HEIs). It is believed that KS and Innovation are also inter-related and could influence organizational performance, especially when HEIs are perceived as the main players of knowledge creation and utilization. KS has been found to be helpful for various organizations particularly for the improvement of resolution through innovation capability. Despite, a relatively new field of research, studies on KS based on Information Systems in developed countries is found to be rich. Science and technology is pivotal in the knowledge-based-society and considered as the main driver for social and economic development. Numerous examples can be found among universities in the USA and Europe that focused on institutional innovation through KS practices using ICT to promote knowledge sharing. Germany had launched a programme named “EXIST” while Moscow State University, Russia launched “Formula of Success” for KS practices. However, in developing countries little attention has been given to KS research particularly in academic institutions. Hence, this study explores the idea of academics’ knowledge sharing intentions in developing countries which influence the universities’ performance towards innovation. We propose a conceptual model comprising of three-dimensions; individual, organizational and technological factors that contribute to knowledge sharing activities drawing from a model and related literature from previous studies. It comprises the Theory of Planned Behaviour, Theory of Reasoned Action and also Social Capital Theory that are being intensively used for higher education research in Europe. It is hoped that the model can help improve understanding of KS intention and innovation among HEIs in developing countries. If this framework is implemented, it might provide the participating institutions with a platform to fit in and disseminate resources for better innovation and decision making process in the HEIs.